Legal Authority of Regional Governments in Mineral Mining Licensing: Justice and Welfare Perspectives in Southeast Sulawesi, Indonesia - Sabri Guntur (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Recentralization of Mining Business License (IUP) authority under Law No. 3 of 2020 has generated legal and governance concerns regarding regional autonomy and distributive justice. Objectives: This study examines the legal basis, historical development, and effectiveness of regional mining licensing authority in Indonesia. Methods: A qualitative socio-legal approach combined normative legal analysis with empirical data from interviews and regional revenue statistics in Southeast Sulawesi. Results: Findings indicate that regional licensing authority is constitutionally grounded, while recentralization has reduced regional mining revenues and created normative conflicts with decentralization principles. Legal substance, territorial characteristics, institutional capacity, and legal culture significantly influence licensing effectiveness. Conclusion: Restoring provincial authority over metallic mineral licensing is necessary to promote distributive justice, strengthen regional welfare, and improve governance. Keywords: regional government authority; mineral mining licensing; distributive justice; decentralization.